Implementasi Insolvency Test Dalam Menyatakan Debitur Pailit Berdasarkan Hukum Kepailitan di Indonesia - Fuad, Assyifa; Paidi Aritonang, Parulian (LPPM Universitas Ekasakti Padang, 2024)
A bankruptcy application can be submitted by the debtor or creditor with a minimal prerequisite, namely having at least 2 (two) creditors and having a debt that has fallen due and is payable in accordance with the provisions of Article 2 paragraph 1 of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (“The Bankruptcy Law”). The ease of filing bankruptcy petitions has raised concerns about its potential to disadvantage debtors and perpetuate malpractices among bankruptcy petitioners. This concern is particularly evident in cases where debtors possess assets that exceed their outstanding debts, rendering them solvent rather than insolvent. A prime example of this issue is the landmark case of Putusan Pengadilan Niaga 48/Pailit/2012/PN.Niaga.Jkt.Pst, where the Commercial Court declared PT Telkomsel bankrupt without first establishing or obtaining evidence that PT Telkomsel's assets were less than its debt to PT PJI, thereby placing it in a state of insolvency. Based on this, the Author will examine the necessity of implementing an insolvency test whose provisions are currently adopted in Government Regulation Number 74 of 2020 regarding the Investment Management Institution.